Revision of the subgenus Diphaomyia Vargas of Culicoides Latreille from India with description of a new species (Diptera: Ceratopogonidae) - Nandi, Mou; Mazumdar, Abhijit (Zootaxa, 2014)
Indian species of Culicoides Latreille, subgenus Diphaomyia Vargas are revised. The Clavipalpis group sensu Wirth & Hubert is transferred to the subgenus Diphaomyia with revised diagnoses of the subgenus and species groups. One species, C. peculiaris has been removed from the subgenus Diphaomyia, the remaining species are freshly reviewed with description of a new one, Culicoides (Diphaomyia) soleamaculatus sp. n. A key to the Indian species of Diphaomyia is presented here.